2022
DOI: 10.1093/intqhc/mzac059
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of employee engagement and patient safety

Abstract: Background Health service administrators are continually investigating new ways to improve the safety and quality of health services. A positive and powerful relationship between employee engagement and patient safety has been suggested in the research literature, and steps can be taken by employers to enhance engagement to improve the safety of health services, particularly considering the COVID-19 pandemic. Methods A review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In addition, one of the inclusion criteria in this study was that publications should be in English. This criterion means that we did not synthesize the results of articles in other languages, and this may result in language bias (Scott et al, 2022 ). However, considering that the data of the included studies are from the Asian, Middle Eastern, European, and American health systems, it can be said that this situation does not create a language bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, one of the inclusion criteria in this study was that publications should be in English. This criterion means that we did not synthesize the results of articles in other languages, and this may result in language bias (Scott et al, 2022 ). However, considering that the data of the included studies are from the Asian, Middle Eastern, European, and American health systems, it can be said that this situation does not create a language bias.…”
Section: Discussionmentioning
confidence: 99%
“…The chain effect of these negative changes in the work engagement of healthcare professionals on patient safety is another salient dimension. Thus, the changes in WE and JS impacted employees as well as quality of care in a way that threatens patient safety (Scott et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Work engagement in primary healthcare settings is very important to unlock their true potential [46]. Engagement is positively related to patient care quality and safety outcomes, and thus patients' assessments of the service provision [47,48,49,50]. Various studies have shown that the relationship between workload and work engagement could be positive or negative depending on the country, resource availability and professionals being studied [51,52].…”
Section: A Holistic Model For Phcmentioning
confidence: 99%
“…Te interaction efect of organizational support and core self-evaluation on nurses' work engagement will be statistically signifcant Hypothesis 1e. Te interaction efect of leader empowerment and core self-evaluation on nurses' work engagement will be statistically signifcant An emergent amount of evidence supports that nurses' work engagement is associated with patient-safety outcomes [18,19]. Typical adverse patient-safety outcomes formulated by the American Nurses Association include falls, pressure ulcers, healthcare-associated infections, medication errors, patient complaints, and verbal abuse [20].…”
Section: Introductionmentioning
confidence: 99%